Grassmukha on the pillars of Antarala - Temples of India Project Team (Jio Institute, 2024)
Grassmukha (face of glory) on the pillars of antarala (vestibule) of the Sitaleshwar Temple (left) and a similar depiction on the ceiling of Cave 1, Ajanta (right). Image source: Ghosh, A. Ajanta Murals. Delhi: Archaeological Survey of India, 1996.